Seller reputation impact on sales performance in public e-marketplace Bukalapak - M. Ammar Fauzan; Amna Shifia Nisafani; Arif Wibisono (Universitas Ahmad Dahlan, 2019)
Seller reputation system (SRS) is an online facility in the public e-marketplace to assess how trustworthy a seller is. SRS becomes important for customers to increase transactional confidence and help customers avoiding untrustworthy sellers. Previous research indicates that different countries with different cultures will lead to different results on how seller reputation influence sales performance. This study aims to investigate the impact of seller reputation on the number of sales in the context of the Indonesian market. This research uses Bukalapak as the case study, which the majority of its customers are Indonesian. Further, this study employ multiple regression analysis on smartphone sales data. The result shows that in Indonesian online market context, the number of seller’s followers does not affect sales number. Furthermore, price and seller positive reviews have a significant impact on sales performance. This study provides insight for sellers in the Indonesian marketplace on how to improve sales performance based on seller reputation.